Adsorption of thiotepa on B12N12, Mg12O12, and Si12C12 fullerene-like cages: A DFT study - Mahboubeh Pishnamazi; Majed Ahmed Algarni; Abdullah Ali Alshehri; Humood Al Shmrany; Sameer Alshehri (Case Studies in Thermal Engineering)
We examined the adsorption of thiotepa (TTP) on the outer surface of B12N12, Mg12O12, and Si12C12 fullerene-like cages using density functional theory (DFT) calculations. The computations were carried out at the Perdew-Burke-Ernzerhof level with the D3 dispersion correction (PBE-D3) in a water solvent. The adsorption mechanism of TTP through N-head and S-head on the external surface of Si12C12 involves a covalent interaction (binding energy ∼ −1.31 eV) with the carrier surface. In contrast, the adsorption of the TTP molecule through N-head and S-head on the outer surfaces of B12N12 (binding energy ∼ −0.75 eV) and Mg12O12 (binding energy ∼ −0.62 eV) fullerene-like cages is driven by electrostatic interactions. Therefore, due to their low values of recovery time, both B12N12 and Mg12O12 fullerene-like cages can serve as carriers for TTP in the treatment of cancer. Thermodynamic parameters (Gibbs free energy and enthalpy energy) demonstrate that these interactions are exothermic and spontaneous. The results further reveal the significant disparity in the calculated HOMO and LUMO energies at the computational level. The formation of intricate bonds between the drug and the fullerene-like cages is attributed to the charge transfer dynamics that occur during their interactions. Through computational analysis and examination of the total density of state (TDOS) plots, it is evident that B12N12 and Si12C12 fullerene-like cages exhibit a high degree of sensitivity to the TTP drug. The adsorption process can increase the electrical conductivity of B12N12 and Si12C12, while having minimal effect on Mg12O12. This suggests that B12N12 could potentially serve as a suitable biosensor for detecting TTP.